2015
DOI: 10.1007/s13187-014-0764-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Community-Partnered Cancer Clinical Trials Pilot Intervention with African American Communities

Abstract: Objectives Cancer Clinical Trial (CCT) accrual and retention rates remain disproportionately low among African Americans. Awareness and access to trials are crucial facilitators of trial participation. Strategies developed within a community-based participatory framework (CBPR) are potential solutions to increase awareness and access to CCTs. In this study, we describe the pilot phase of three innovative community-centered modules to improve basic CCT knowledge, awareness of locations to access CCT information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…Based on the model, awareness barriers can include limited information about cancer and lack of awareness or knowledge of clinical trials (Green et al, 2015; Haynes-Maslow et al, 2014; Leiter, Diefenbach, Doucette, Oh, & Galsky, 2015). These factors could be major contributors to lower participation rates in cancer clinical trials among racially and ethnically diverse populations.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the model, awareness barriers can include limited information about cancer and lack of awareness or knowledge of clinical trials (Green et al, 2015; Haynes-Maslow et al, 2014; Leiter, Diefenbach, Doucette, Oh, & Galsky, 2015). These factors could be major contributors to lower participation rates in cancer clinical trials among racially and ethnically diverse populations.…”
Section: Methodsmentioning
confidence: 99%
“…The SISTAS Research Study -Bevel et al for high-risk populations, such as AA women, have been shown to reduce obesity and adverse health outcomes associated with added weight. 38 Most cancer-based CBPR interventions focus on screening for cancer to combat health disparities, 39,40 promotion of general overall health, 41 or participation rates among AAs. 42 The SISTAS trial is unique for several reasons.…”
Section: Interventions That Are Personalizedmentioning
confidence: 99%
“…Participants in the current study echoed similar recommendations. Another study found role‐playing and call‐and‐response sessions aimed at dispelling myths and providing facts about clinical research were educational interventions that increased favourable attitudes about clinical research and WTP 46 . Community engagement activities could build capacity related to knowledge of scientific methods and study designs, so once research opportunities present themselves, people feel more knowledgeable and confident to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%